2016
DOI: 10.1007/s11095-016-1872-x
|View full text |Cite
|
Sign up to set email alerts
|

Lomustine Nanoparticles Enable Both Bone Marrow Sparing and High Brain Drug Levels – A Strategy for Brain Cancer Treatments

Abstract: PurposeThe blood brain barrier compromises glioblastoma chemotherapy. However high blood concentrations of lipophilic, alkylating drugs result in brain uptake, but cause myelosuppression. We hypothesised that nanoparticles could achieve therapeutic brain concentrations without dose-limiting myelosuppression.MethodsMice were dosed with either intravenous lomustine Molecular Envelope Technology (MET) nanoparticles (13 mg kg−1) or ethanolic lomustine (6.5 mg kg−1) and tissues analysed. Efficacy was assessed in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…However, it carries a 30% risk of causing severe hematological toxicity, so it is suggested only as the second-line treatment for recurrent GBM [ 5 ]. It is likely that the first-line agent for GBM, temozolomide, also carries a risk of dose-limiting bone marrow suppression [ 3 ]. Moreover, Houshyari et al concluded that systemic chemotherapy has no significant survival benefit for patients with GBM [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it carries a 30% risk of causing severe hematological toxicity, so it is suggested only as the second-line treatment for recurrent GBM [ 5 ]. It is likely that the first-line agent for GBM, temozolomide, also carries a risk of dose-limiting bone marrow suppression [ 3 ]. Moreover, Houshyari et al concluded that systemic chemotherapy has no significant survival benefit for patients with GBM [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
“…In order to bypass the detrimental hematotoxic effects of the current systemic chemotherapeutic regimen, many promising technologies have recently emerged, including the direct placing of Gliadel wafers (Arbor Pharmaceuticals, Atlanta, Georgia, US), a set of biological polymer discs containing carmustine, a nitrosourea, within the brain following tumor resection, and Molecular Envelope Technology (MET) nanoparticles [ 3 , 7 - 9 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…GCPQ consists of a glucosamine sugar backbone where, a fraction of the amine groups have been functionalised with either a long chained hydrophobic pendant group or a quaternary ammonium cation. Functionalisation in this way creates an amphiphilic polymer which self assembles into nanoparticles [35] and which enables drugs to cross biological barriers to produce formulations with a number of differentiating features [36][37][38]. The cationic polymer binds to the anionic surface of the precipitated SPIONs to form stable nano-sized clusters.…”
Section: Introductionmentioning
confidence: 99%